Parameterisation and validation of a resource budget model for masting using spatiotemporal flowering data of individual trees. (24th July 2016) - Abe, Tomoyuki; Tachiki, Yuuya; Kon, Hirokazu; Nagasaka, Akiko; Onodera, Kensuke; Minamino, Kazuhiro; Han, Qingmin; Satake, Akiko
Abstract: Synchronised and fluctuating reproduction by plant populations, called masting, is widespread in diverse taxonomic groups. Here, we propose a new method to explore the proximate mechanism of masting by combining spatiotemporal flowering data, biochemical analysis of resource allocation and mathematical modelling. Flowering data of 170 trees over 13 years showed the emergence of clustering with trees in a given cluster mutually synchronised in reproduction, which was successfully explained by resource budget models. Analysis of resources invested in the development of reproductive organs showed that parametric values used in the model are significantly different between nitrogen and carbon. Using a fully parameterised model, we showed that the observed flowering pattern is explained only when the interplay between nitrogen dynamics and climatic cues was considered. This result indicates that our approach successfully identified resource type‐specific roles on masting and that the method is suitable for a wide range of plant species.